The Healthcare Workers’ Dissatisfaction Factors on Employment Contract in Malaysia: A Systematic Review - Anis Syafiqah Abd Razak; Osman Ali (Asian Journal of Medicine & Health Sciences, 2023)
The introduction of a contract employment system for doctors in 2016 in Malaysia has raised widespread discontentment regarding the precarious nature of employment for contract doctors. There has been an increasing job dissatisfaction and decreasing job satisfaction among the contract doctors. The displeasure has led to a negative impact on the health services including high resignations, absenteeism, and protests when dialogue and discussion fail to address these issues. The review aimed to identify various satisfaction and dissatisfaction factors associated with the contract employment system in different countries that practiced the system. Literature and citations are systematically searched in the databases of PubMed, Cochrane Library, Wiley Online Library, Elsevier’s Scopus, and Google Scholar. The articles contain an empirical study in the English language, published after year 2000, with at least one factor of satisfaction or dissatisfaction and subjected to methodology quality appraisal using methodological criteria. Thirteen eligible articles were reviewed. It was found that the intrinsic job satisfaction factors that are mostly mentioned in many studies were job performance and working experience. The extrinsic job satisfaction factors were mainly the aspects related to the organization, career advancement and inter-relationship between co-workers. In terms of intrinsic job dissatisfaction, the feeling of insecurity about the job and emotional exhaustion were identified. The extrinsic job dissatisfaction includes career advancement policy, and provision of facilities and infrastructure. Salary, social security payments and working time were identified as the extrinsic factors for both job satisfaction and dissatisfaction. However, there was lack of consistency in the findings between studies on the factors associated with satisfaction or dissatisfaction. This review provides evidence of the presence of intrinsic and extrinsic factors of job satisfaction and dissatisfaction among the contract workers. However, the study did not seek the acceptability of the system by the contract workers. Most of factors identified were common to all professions such as remuneration, benefits, and workload, so administrative solution should be sought to address the issues. Attention by higher authorities should be given to the feeling of insecurity about the job, career advancement and emotional exhaustion experienced by contract doctors.